Emotional Dynamics and Potential Burnout of Indonesian EFL Teachers Amid Uncertainty in Curriculum Change in Private Schools - baiq nadia ulfa sari nadia; Amin Muhammad; Thohir Lalu; Mahyuni Mahyuni (Program Studi Pendidikan Bahasa Inggris, 2026)
This study aims to analyze the emotional dynamics and potential burnout of English as a Foreign Language (EFL) teachers in Indonesian private schools in the face of curriculum reform uncertainty. The educational policy shift, particularly the transition from Curriculum 2013 to the Merdeka Curriculum, has posed both professional and emotional challenges for teachers. Employing a mixed-methods approach with an explanatory sequential design, this research integrates quantitative analysis using Likert-scale questionnaires with qualitative data from open-ended responses. The participants consisted of 12 EFL teachers from private schools in West Nusa Tenggara Province, selected based on their teaching experience in the context of curriculum change. Findings indicate that while teachers experienced negative emotions such as anxiety and frustration, they also demonstrated positive emotions, particularly hope and optimism, which recorded the highest average scores. Curriculum uncertainty significantly influenced professional performance, especially in lesson planning, motivation, and teaching effectiveness. Teachers’ burnout levels tended to be high, although Spearman’s correlation test showed a weak and statistically insignificant relationship between curriculum uncertainty and burnout. Nevertheless, qualitative findings revealed evident emotional strain among several teachers, including mental fatigue, administrative burdens, and considerations of leaving the profession. Overall, this study highlights that curriculum reform is not merely a structural transformation but also an emotional experience with direct implications for teachers’ well-being, thus emphasizing the need for institutional support, policy clarity, and training programs that strengthen teachers’ emotional resilience and professional adaptability in navigating educational reforms.